Views of government and non-government actors on urban forest management and governance in ten Latin-American capital cities - Orozco Aguilar, Luis; y otros siete autores más (Elsevier, 2023)
Addressing urban forest management and governance challenges is fundamental for implementing urban forest policies. Most of the evidence on this topic comes from Global North cities, so little is known about how urban forest management and governance are experienced by urban forest actors in Global South cities, including Latin American and the Caribbean (LAC) cities. This study aimed to assess the views of urban forest actors in LAC cities on how they participate in collective decision-making, the current state of urban forest management and governance, and contact among actors, with a focus on how these views related to each other and differences among government and non-government actors. We designed and delivered an online survey to government and non-government actors in ten LAC capital cities, including Bogotá, Brasília, Buenos Aires, Ciudad de México, Ciudad de Panamá, La Paz, Lima, San José , San Juan, and Santiago de Chile. We analysed 155 responses using regression-based techniques. We found that more contact among actors resulted in more participation in collective decision making and more optimistic views about the state of urban forest management and governance. Also, more optimistic views about the state of urban forest management and governance resulted in more trust in local governments. Non-government actors had lower levels of trust in local governments than government actors. We discuss how implementing urban forest policies does not solely depend on having enough resources (e.g., finances, personnel) but also on engaging in collective decision-making and improving trust in the institutions in charge of implementing urban forest policies.